Charkin hits WHS. (Bookseller, 2005)
This article reports that Richard Charkin, Macmillan CEO and president of the Publishers Association, has hit out at W H Smith over its attempts to fine publishers for late deliveries. Charkin stated that the fines would complicate the supply chain and add unnecessary costs, after the rest of the industry had worked to improve efficiency. It is informed that negotiations between publishers and the chain's commercial director Tim Clifford over the fines and terms continued this week. No legal proceedings have yet been issued, and no publishers are thought to have ceased supply.